2014
DOI: 10.1159/000365415
|View full text |Cite
|
Sign up to set email alerts
|

Can Serum Pin1 Level Be Regarded as an Indicative Marker of Nonalcoholic Steatohepatitis and Fibrotic Stages?

Abstract: Background: We aimed to investigate serum Pin1 as an indicator of the presence of nonalcoholic steatohepatitis (NASH) and its association with the histopathological liver fibrosis stages. Methods: Serum samples were collected from consecutive biopsy-proven NASH patients and healthy controls, and then serum levels of Pin1 were measured. The correlations between clinical and histopathological features of NASH and Pin1 were evaluated. Patients who had fibrotic stages <2 were termed mild fibrosis group and those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 37 publications
(49 reference statements)
0
19
0
Order By: Relevance
“…Liver biopsy should not be advised as a population screening technique as numerous noninvasive fibrosis markers have already been defined. As there is an increasing need for noninvasive markers in predicting liver fibrosis, numerous markers have been described to be related to liver fibrosis, although there is a definite gap in this area [9][10][11][12]. Because of the absence of acceptable treatment methods for NAFLD, attention needs to be paid to the identification of significant liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Liver biopsy should not be advised as a population screening technique as numerous noninvasive fibrosis markers have already been defined. As there is an increasing need for noninvasive markers in predicting liver fibrosis, numerous markers have been described to be related to liver fibrosis, although there is a definite gap in this area [9][10][11][12]. Because of the absence of acceptable treatment methods for NAFLD, attention needs to be paid to the identification of significant liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…These scores consist of easily available and applicable variables, such as aspartate aminotransferase (AST) to alanine aminotransferase (ALT) ratio (AAR), AST to platelet ratio index (APRI), fibrosis index (FI), fibrosis cirrhosis index (FCI), and fibrosis 4 (FIB‐4) score . As there is a growing necessity of non‐invasive markers in predicting fibrosis, various markers have been reported to be associated with liver fibrosis, although there is a clear lack in this field …”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have shown serum Pin1 concentrations to be highly correlated with the progression of metabolic syndromes [21,22].…”
Section: Introductionmentioning
confidence: 99%